Crossroads of Culture : Christianity, Ancestral Spiritualism, and the Search for Wellness in Northern Malawi - Lindland, Eric (Mzuni books, 2020)
Combining history, ethnography, and culture theory, this book explores how residents in northwestern Malawi have responded over time to the early missionary assertion that local religious and healing practices were incompatible with Christianity and western medicine. It details how local agents, in the past and today, have constructed new cultural forms that weave facets of ancestral spiritualism and divination with Christianity and biomedicine. Alongside a rich historical review of the late-19th century encounter between Tumbuka-speakers and the Scottish Presbyterians of the Livingstonia Mission, the book explores the contemporary therapeutic dance complex known as Vimbuza and considers two case studies, each the story of a man confronting illness and struggling to understand the roots and meaning of his affliction. In the process, the book considers the enduring missiological and anthropological topics of conversion and syncretism, and questions the assertion by some scholars that Western missionaries in Africa have been successful agents of religious hegemony.